Problems Encountered by Learners and How to Deal with Them in Learning English as A Foreign Language - NURAENI NURAENI (UICELL, 2019)
In the process of learning English, EFL learners undergo many difficulties and give negative attitude towards the language. This research is conducted to respond this phenomenon. The aim of this research is to find out problems encountered by students who learn English as a foreign language and how they cope with the problems. This research uses qualitative approach in order to understand the phenomenon and uses interview as the research tool to gather data. The participants of this research are EFL learners who experience difficulties in learning English. In analysing the data, thematic analysis is used. From the findings, the data reveal that difficulties encountered by the students are varied which are grouped into themes: problem with grammar, problem with pronunciation, and problem with academic writing. In dealing with the problems, the participants use some different ways: autonomous learning, family and friends support, lectures as role models, and be diligent. Key words: EFL, Foreign Language Learning, Teaching English as A Foreign Language, Problems in Leaning English